Community members and healthcare workers' priorities for the control and prevention of snakebite envenoming in Ghana. - Leslie Mawuli Aglanu; John Humphrey Amuasi; Evie Prokesh; Alexis Beyuo; Chrisantus Danaah Dari; Sofanne J Ravensbergen; Melvin Katey Agbogbatey; Austin Gideon Adobasom-Anane; Kabiru Mohammed Abass; David G Lalloo; Jörg Blessmann; Benno Kreuels; et al. (Public Library of Science (PLoS), 2023)
Introduction Snakebite is one of the most neglected tropical diseases. In Ghana, there has been a limited interest in snakebite envenoming research despite evidence of high human-snake conflicts. In an effort to meet the World Health Organisation's (WHO) 2030 snakebite targets, the need for research evidence to guide policy interventions is evident. However, in setting the research agenda, community and healthcare workers' priorities are rarely considered. Methods Three categories of focus groups were formed in the Ashanti and Upper West regions of Ghana, comprising of community members with and without a history of snakebite and healthcare workers who manage snakebite patients. Two separate focus group discussions were conducted with each group in each region. Using the thematic content analysis approach, the framework method was adopted for the data analysis. A predefined 15-item list of potential snakebite-associated difficulties and the WHO's 2030 snakebite strategic key activities were ranked in order of priority based on the participants' individual assessment. Results Both acute and chronic effects of snakebite such as bite site management, rehabilitation and mental health were prioritised by the community members. Health system challenges including training, local standard treatment protocols and clinical investigations on the efficacy of available antivenoms were identified as priorities by the healthcare workers. Notably, all the participant groups highlighted the need for research into the efficacy of traditional medicines and how to promote collaborative strategies between traditional and allopathic treatment practices. Conclusion The prioritisation of chronic snakebite envenoming challenges by community members and how to live and cope with such conditions accentuate the lack of post-hospital treatment follow-ups for both mental and physical rehabilitation. To improve the quality of life of patients, it is essential to involve grassroots stakeholders in the process of developing and prioritising future research agenda.